Probiotics for the Treatment of Atopic Dermatitis in Children: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Huang, Ruixue; Ning, Huacheng; Shen, Minxue; Li, Jie; Zhang, Jianglin; Chen, Xiang (Frontiers in Cellular and Infection Microbiology, 2017)
Objective: Atopic dermatitis (AD) is a prevalent, burdensome, and psychologically important pediatric concern. It has been reported that the intervention of interest is the use of probiotics for treatment of AD in children. Some reports have assessed the efficacy of probiotics in AD in children; however, evidence for their use has yet to be firmly established. Methods: To assess the effects of probiotics on AD in children, the PubMed/Medline, Cochrane Library Scopus, and OVID databases were searched for reports published in the English language. Results: Thirteen studies were identified. Significantly higher SCORAD values favoring probiotics over controls were observed (mean difference [MD], –3.07; 95% confidence interval [CI], –6.12 to –0.03; P < 0.001). The reported efficacy of probiotics in children < 1 year old was –1.03 (95%CI, –7.05 to 4.99) and that in children 1–18 years old was –4.50 (95%CI, –7.45 to –1.54; P < 0.001). Subgroup assessment showed in Europe, no effect of probiotics on SCORAD, whereas significantly lower SCORAD values were reported for Asia (MD, –5.39; 95%CI, –8.91 to –1.87). Lactobacillus rhamnosus GG (MD, 3.29; 95%CI, –0.30 to 6.88; P = 0.07) and Lactobacillus plantarum (MD, –0.70; 95%CI, –2.30 to 0.90; P = 0.39) showed no significant effect on SCORAD values in children with AD. However, Lactobacillus fermentum (MD, –11.42; 95%CI, –13.81 to –9.04), Lactobacillus salivarius (MD, –7.21; 95%CI, –9.63 to –4.78), and a mixture of different strains (MD, –3.52; 95%CI, –5.61 to –1.44) showed significant effects on SCORAD values in children with AD. Conclusions: Finding from this meta-analysis might not draw a robust conclusion that probiotics have beneficial effects on treating children with AD. Moreover, caution is needed when generalizing our results due to heterogeneity in the populations studied. More adequately powered randomized controlled trials involving larger samples are necessary to determine which species of probiotics and dosages and what periods of treatment are most efficacious against AD in children.